PREVALENCE AND PATTERN OF INJURY IN SEXUAL ASSAULT CASES PRESENTED AT KHYBER MEDICAL COLLEGE PESHAWAR - Nadeem, Faiza; Muhammad Wasif,; Iftikhar Ahmad,; Ahsan Ali,; Salma Shazia,; Omair Jadoon, (Journal of Ayub Medical College Abbottabad, 2024)
Background: Actual or threatened physical intrusion of a sexual nature, whether by force or under unequal or coercive conditions. Nowadays sexual assault is considered a major public health issue all over the world, especially in developing countries. Sexual abuse is declared as a medical emergency. Sexual abuse cases are examined in Pakistan by medico-legal officers and their findings are presented to the court as evidence and medico-legal officers present to the court as witness. The objectives were to find out the prevalence of sexual assault cases presented to the forensic medicine department Khyber Medical College Peshawar and to find out the most prevalent pattern of genital and extragenital injury. To find out the association between sexual assault and its associated demographic factors such as age, gender, and drug history. Methods: This descriptive cross-sectional was conducted in the Department of Forensic Medicine and Toxicology from 1st January 2023 to 31st December 2023. All cases of any gender and age were included in the study and cases referred from other districts and with incomplete documentation were excluded. Results: In 90 subjects, the males were 35.6% (n=32), whereas females were 64.4% (n=54). Of the subjects, 72.2% (n=65) had attempts of sexual assault, out of which 43.3% (n=39) went through rape and 28.9% (n=26) went through sodomy. 17.8% (n=16) had associated genital injuries with the assault while 10.0% (n=9) had extragenital injuries. The concurrent poisoning seen was 2.2% (n=2) which was merely benzodiazepine in cases of sexual assault. Conclusion: Our data concluded that sexual assault was more prevalent in females than in males. Most of the individuals were from urban areas rather than rural areas. Of the subjects, rape was more prevalent than sodomy. The most common pattern of genital injury is anal tear while extragenital injuries vary from bruises to abrasions on various parts of the body. The most common drug used was benzodiazepines.